2000
DOI: 10.1046/j.1365-3059.2000.00451.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic variability of Leptosphaeria lindquistii (anamorph: Phoma macdonaldii), a fungal pathogen of sunflower

Abstract: Growth of 17 isolates of Phoma macdonaldii, the causal agent of sunflower black stem, was investigated for response to pH and temperature, and for morphology and asexual morphogenesis (pycnidiogenesis and pycnidium size). For all isolates, the optimum pH for growth was between 4 and 5, and the optimum temperature varied between 20 and 30ЊC and radial growth was slowest at 5 and 35ЊC. Significant differences in the number and size of pycnidia were observed between isolates. Pycniospore germination was investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 16 publications
3
33
1
1
Order By: Relevance
“…In addition, they showed that the behaviour of sunflower genotypes in controlled conditions remained unchanged irrespective of the phenological stage reached at the time of inoculation. Most of field testing is usually done at the stage R3-R5 (Carson, 1991;Sessau et al, 2008), as we did as well, but a vast majority of studies have been done in controlled conditions (Mirić et al, 1999;Roustaee et al, 2000a). Furthermore, our results from the non-irrigated field, compared to the irrigated one, are in concordance with the results of Sessau et al (2010), who found a positive correlation between water stress and P. macdonaldii attack severity.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In addition, they showed that the behaviour of sunflower genotypes in controlled conditions remained unchanged irrespective of the phenological stage reached at the time of inoculation. Most of field testing is usually done at the stage R3-R5 (Carson, 1991;Sessau et al, 2008), as we did as well, but a vast majority of studies have been done in controlled conditions (Mirić et al, 1999;Roustaee et al, 2000a). Furthermore, our results from the non-irrigated field, compared to the irrigated one, are in concordance with the results of Sessau et al (2010), who found a positive correlation between water stress and P. macdonaldii attack severity.…”
Section: Resultssupporting
confidence: 87%
“…Besides differences in sunflower genotype response, certain variability has also been proved to exist among different isolates of the fungus (Roustaee et al, 2000a;Larfeil et al, 2002). Therefore, accurate knowledge of the pathogen variability is also required for identification of tolerant genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…The constancy of ranking of isolates over the two experiments in this study provides further strong evidence for this claim. Similar variation in aggressiveness was demonstrated among isolates of P. macdonaldii originating from different geographical locations based on pathogenicity tests on cotyledon petioles (Roustaee et al, 2000b;Larfeil et al, 2002).…”
Section: Discussionsupporting
confidence: 65%
“…According to Roustaee et al, (2001) for 17 isolates of Phoma macdonaldii, the causal agent of sunflower black stem, the optimum pH for growth was between 4 and 5 but in the present study none of the isolates were found to grow at best at that pH.…”
Section: Effect Of Different Phcontrasting
confidence: 60%
“…In the past Nebane and Ekpo (1995) investigated the effects of temperature on radial growth and pycnidium production of cowpea (Vigna unguiculata) isolates (PB1, PB2, PB3) of Phoma bakeriana in vitro and found that maximum growth and pycnidium production occurred at 25 0 C. The optimum temperature range was 20C to 28 0 C for the growth of Phoma as deduced by KueiMai (2000). Roustaee et al, (2001) evaluated the growth of 17 isolates of Phoma macdonaldii, the causal agent of sunflower black stem and investigated for response to temperature and for morphology and asexual morphogenesis (pycnidiogenesis and pycnidium size). They concluded that the optimum temperature varied between 20 and 30°C and radial growth was slowest at 5 and 35°C.…”
Section: Effect Of Different Temperaturementioning
confidence: 99%